INVESTIGATE THE FACTORS THAT AFFECT CHAGES IN STOCK PRICES Empirical study on listed companies in Indonesia stock exchange multi industrial Companies 2015- 2019 - Muchilis, Tanti Irawati (CENTRAL ASIA AND THE CAUCASUS, 2022)
Changes in stock price and developments in the currents ratio (CR), total asset turnover (TATO), and net profit margin (NPM) in various industrial companies listed on the Indonesia stock exchange have fluctuated increases and depresses. Serval theories and studies say that changes in stock prices are influenced by the current ratio (CR), total assets turnover (TATO) variables and net profit margin (NPM). After the author Analysis and find that there are discrepancies and different form several research results and there are facts that contradict the existing theory. Therefore the authors make study that aims to analysis the effect of the currents ratio (CR), total asset turnover (TATO) and net profit margin (NPM) on changes in stock prices in various industrial companies listed on the Indonesian stock exchanges (IDX) period, 2015-2019. The research method used in this study is to use the historical methods the sampling methods used purposive sampling, so that there were 29 companies sampled in this study. The analytical method used is the panel data regression methods. Statistical analysis used t test for partial test which first tested the classical assumption test which consisted of normality, multicollinearity, heteroscedasticity and autocorrelation test. The results of the t test carried out are the currents ratio (CR) , total asset turnover (TATO) and net profit margin (NPM).